Kenya’s State Department of Livestock catalyzes investments of USD 223 million in the dairy sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Kenya’s State Department of Livestock is catalyzing investments of USD 223 million in Kenya’s dairy sector, based on CCAFS research and support, for the development of a Nationally Appropriate Mitigation Action (NAMA) in the dairy sector. After a two-year process, the government of Kenya has reached an agreement with the World Bank to submit the NAMA concept note to the Green Climate Fund.